Source Term Analysis of Small Long-Life without Refueling 420 MWt PWR during Loss of Coolant Accident (LOCA) - M. I. A. Abidin; Zaki Su'ud; Ari Darmawan Pasek (Institut Teknologi Bandung, 2010)
Source term analysis of a small long-life 420 MWt PWR has been performed. The analysis includes calculation of fission products inventory in the core, the core activity, source term activity and toxicity, and also dose calculation on various situations during LOCA. Diffussion calculation conducted during the Beginning of Life (BOL) of the reactor. LOCA scheme calculated when the reactor has been operated for 10080 full power days. Fission products activities in the core have a total of 3.2E+08 Ci. Fission product activity that are released to the environment with assumption that 100% of noble gas, 50% of halogens and 1% of other source term groups are released resulting in a total activity of 6.71E+05 Ci, or about 0.21% of total activity in the core. Toxicity analysis show that there are 200 nuclides released to the atmosphere categorized as dangerous. Calculation of thyroid dose in the boundary of exclusion zone (350 m) gives result of 0.57593 rem, while in low population zone resulted in 0.23013 rem. Whole body dose calculation in exclusion zone resulted in 0.14583 rem and in low population zone, the whole body dose is 0.05107 rem.